Mercury emissions, hazards and preventive measures: A review - Abbas, T. (CRC Press, 2015)
The impact of mercury emission on environment by natural and anthropogenic sources makes the global village worried recently. In particularly, in Europe, its level of emission is quite high due to power plants and their industrial processes. Thus, more attention is paid to it on account of its potential hazard for workers and environment. It is vital that its level of pollution should be decreased by emission sources. The paper highlights the basic mercury sources in Europe. It also provides details about transportation of mercury into human body via different systems. Moreover, the associated hazards and preventive steps are widely discussed. Finally, mercury removal technologies are presented. Â© 2015 Taylor & Francis Group, London.